A survey of knowledge about the MTA properties amongst internship students - Habib, Adnan; Doumani, Mazen; Mossa, Hossam; Bashnakli, Ahmad Reda; Ibrahim, Ali Nader (International Journal of Dental Research, 2017)
Objective: The aim of this study was to assess the knowledge of the mineral trioxide aggregate (MTA) properties among internship students in Riyadh city, Saudi Arabia.Methods: A standardized questionnaire comprised 14 multiple-choice questions about MTAproperties distributed to internship students in Riyadh city,Saudi Arabia. These questions contained types of MTA material, mechanical, chemical, physical properties of MTA, marginal adaptation and sealing ability, antibacterial properties, reaction with other dental materials, biocompatibility, and clinical    performance. Data was coded computerized and analyzed using methods of descriptive statistics.Results: The respondents of this questionnaire were 195 subjects. 51.5% of subjects confirmed that MTA sets in the presence of water. 69.4% of respondents confirmed that MTA is available as white and grey. Majority of subjects asserted the sealing ability (89.5%) and antibacterial effects (71.6%) of MTA material. The vast majority don’t know the mixing time (50.6%), and pH of MTA (52%).Conclusion: It has been observed an average knowledge about mineral trioxide aggregate (MTA) , an  increased  knowledge about sealing ability and anti-bacterial effects , and poor  knowledge about manipulation of MTA material amongst internship students .